Learning or Distraction? Explaining TikTok and Snapchat Use among Communication Students through the Affordance–Motivation–Context Heuristic - Abubakar Sufyanu Saidu Al-Sadique; Adamkolo Ibrahim; Umaru A. Pate (PT Agung Media Publisher, 2026)
Platforms such as TikTok and Snapchat are increasingly used not only for entertainment but also as informal environments where students observe communication trends, learn visual storytelling techniques, and experiment with digital content creation. However, the academic implications of these platforms remain debated because they can simultaneously support learning while also creating distractions. This study aims to examine how communication students use TikTok and Snapchat and to explain the relationship between learning opportunities and academic distraction through the Affordance–Motivation–Context (AMC) heuristic. This research employed a qualitative exploratory approach involving communication students who actively use short-form social media platforms. Data were collected through in-depth interviews and reflective observations about students’ media practices in academic and everyday contexts. The data were analyzed thematically to identify patterns of platform use, student motivations, and the influence of technological features on media engagement. The findings reveal three main insights. First, TikTok and Snapchat create a paradoxical outcome in which learning benefits and academic distractions coexist. Students often use these platforms to gain inspiration for digital communication practices, yet they may also experience attention fragmentation due to continuous content streams. Second, platform affordances such as algorithmic recommendations, automatic playback, and creative editing tools significantly shape user behavior. Third, the outcomes of social media use depend on students’ motivations and the educational environment. Students who approach these platforms for creative or professional development tend to experience more positive learning outcomes.